Silahların eşitliği ilkesi - Anaklı, Ender (My University, 2006)
SİLAHLARIN EŞİTLİĞİ İLKESİ ENDER ANAKLI TEZ ÖZETİ Bu tez çalışması ile; İnsan Hakları Avrupa Sözleşmesi’nin 6 ncı maddesi Adil Yargılanma Hakkı kapsamındaki silahların eşitliği ilkesini sözleşme hukuku ve iç hukuk bakımından, karşılaştırmalı olarak incelemek, iç hukukta yapılması gereken değişiklikleri ortaya koyabilmek amaçlanmıştır. Öncelikle insan haklarının ve adil yargılanma hakkının tarihsel gelişimi anlatılmıştır. İkinci bölümde, Türk Ceza Yargılaması kapsamında bilgi ve belgelere ulaşma, tanık dinlenmesi, karşı delil sunma, delilden vazgeçme ve bilirkişi yönünden, İnsan Hakları Avrupa Mahkemesi kararları, mevcut usul hükümleri ve Yargıtay ve Askeri Yargıtay kararları incelenmiştir. Üçüncü bölümde, Türk Özel Hukuku kapsamında bilgi ve belgelere ulaşma, tanık ve bilirkişi yönünden İnsan Hakları Avrupa Mahkemesi kararları, mevcut usul hükümleri ve Yargıtay kararları, Türk İdare Hukuku kapsamında bilgi ve belgelere ulaşma ve bilirkişi yönünden İnsan Hakları Avrupa Mahkemesi kararları, mevcut usul hükümleri ve Danıştay ve Askeri Yüksek İdare Mahkemesi kararları incelenmiştir. Sonuç bölümünde ise mevcut düzenlemelerde yapılması gereken değişiklikler ortaya konmaya çalışılmıştır. SİLAHLARIN EŞİTLİĞİ İLKESİ ENDER ANAKLI

The aim of this study is, to compare the law of contract and domestic law about the equality of arms which explained in the 6th article of European Convention of Human Rigths that explains the right of fair trial and put the case clearly the modification alteration must be done in the domestic law. First the historical development of the concept of human rigths and fair trial will be explained. In second part, to gain intelligence and document, to listen attestant, to offer against evidence, to abondon evidence and expert witness , in Turkish Criminal Trial will be analyzed , according to European Human Rigth Court’ s decision , present procedure arbitrament, and the decisions of Court Of Appeal and Military Court Of Appeal. In third part, to gain intelligence and document, to listen attestant, to offer against evidence, to abondon evidence and expert witness in Turkish Private law will be analyzed according to European Human Rigth Court’ s decision , present procedure arbitrament, and the decisions of Court Of Appeal and also to gain intelligence and document and expert witness in Turkish Administrative Law will be analyzed according to European Human Rigth Court’ s decision , present procedure arbitrament, and the decisions of Turkish Council Of State and Turkish Military Council Of State. In part of result, the necessary modification in present law will be explained.
Keywords: Kamu Hukuku